The effect of virgin nylon addition into recycled nylon on the fatigue strength of thermoplastic nylon denture base - Wahyuni, Siti; Ravichanthiran, Jeewena (Universitas Padjadjaran, 2020)
Introduction: Thermoplastic nylon denture base is processed through injection molding process. This manipulation technique produces non-biodegradable nylon wastes which have to be recycled. Recycling of nylon wastes is feasible due to the linear molecular structure of thermoplastic nylon. This study aimed to know the effect of adding virgin nylon into recycled nylon on the fatigue strength of thermoplastic nylon denture base. Methods: This research was experimental laboratory research using 27 samples of thermoplastic nylon with three different groups (100% virgin nylon, 100% recycled nylon and combination of 60% of virgin nylon with 40% of recycled nylon) using injection molding technique. The test results were analyzed using one-way ANOVA test to know the differences in the mean value of the fatigue strength of each group and LSD test to know the effect of adding 60% of virgin nylon into 40% of recycled nylon. Resuts: Results showed significant results (p < 0,05), as well as LSD test that showed there is effect of adding 60% of virgin nylon into 40% of recycled nylon on the fatigue strength of thermoplastic nylon denture base. Conclusion: The combination of 60% of virgin nylon with 40% of recycled nylon showed higher fatigue strength than the recycled nylon.